2016
DOI: 10.1134/s1063779616040080
|View full text |Cite
|
Sign up to set email alerts
|

Gauge fields, nonlinear realizations, supersymmetry

Abstract: This is a brief survey of the all-years research activity in the Sector "Supersymmetry" (the former Markov Group) at the Bogoliubov Laboratory of Theoretical Physics. The focus is on the issues related to gauge fields, spontaneously broken symmetries in the nonlinear realizations approach, and diverse aspects of supersym

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 174 publications
0
16
0
Order By: Relevance
“…The non-linear transformation of the goldstino is obtained by solving the superfield constraints. This construction is based on the general relation between linear and non-linear realizations of supersymmetry put forward in [22,23,73] (see [74] for a recent review).…”
Section: Description Of the Goldstino In Terms Of Constrained Superfimentioning
confidence: 99%
See 1 more Smart Citation
“…The non-linear transformation of the goldstino is obtained by solving the superfield constraints. This construction is based on the general relation between linear and non-linear realizations of supersymmetry put forward in [22,23,73] (see [74] for a recent review).…”
Section: Description Of the Goldstino In Terms Of Constrained Superfimentioning
confidence: 99%
“…It was further elaborated by Samuel and Wess [26], including its coupling to supergravity. Alternatively, one can construct a spinor superfield directly from the original Volkov-Akulov goldstino [23] (see [66,74] for reviews)…”
Section: Spinor Goldstino Superfieldsmentioning
confidence: 99%
“…The technique used to describe gravity with a nonlinear representation of SL(4, R) and C(1, 3) was proposed in the paper [39]. A more detailed review can be found in [50]. In accordance with Section 3, one should use variables subject to a linear Lorentz transformation to construct nonlinear representations of SL(4, R) and C (1,3).…”
Section: Nonlinear Representation Of Sl(4 R) and C(1 3) On The Viermentioning
confidence: 99%
“…The NL/LSUSY relations are obtained systematically in superspace formalism by means of superfields on specific superspace coordinates depending on the NG fermions [4] (for recent review, see [9]). On the other hand, in the component expression, we have recently discussed a linearization procedure of NLSUSY based on a commutator algebra in the VA NLSUSY theory for extended SUSY [10]: In the VA NLSUSY theory, the NLSUSY action describing dynamics of NG fermions is defined from a fundamental determinant which corresponds to both a spontaneous SUSY breaking and a basic geometrical structure of spacetime with Grassmann coordinates.…”
mentioning
confidence: 99%